P102 Development of a Novel Assay for the Detection of Active Neutrophil Elastase in Patients with Chronic Obstructive Pulmonary Disease. (12th November 2015) - Moffitt, KL; Martin, SL; Chalmers, J; Walker, B
Abstract : Neutrophil elastase (NE), a biomarker of infection and inflammation, correlates with the severity of several respiratory diseases including chronic obstructive pulmonary disease (COPD). However, it's detection and quantification in biological samples is confounded by a lack of reliable and robust methodologies. Standard assays using chromogenic or fluorogenic substrates are not specific when added to complex clinical samples containing multiple proteolytic and hydrolytic enzymes which have the ability to hydrolyse the substrate, thereby resulting in an over-estimation of the target protease. Furthermore, ELISA systems measure total protease levels which can be a mixture of latent, active and protease-inhibitor complexes. Therefore, we have developed a novel immunoassay (ProteaseTag™ Active NE Immunoassay) which is selective and specific for the capture of active NE in sputum and Bronchoalveolar Lavage (BAL) in patients with COPD. The objective of this study was to clinically validate ProteaseTag™ Active NE Ultra Immunoassay for the detection of NE in sputum from COPD patients. 20 matched sputum sol samples were collected from 10 COPD patients (M = 6, F = 4; 73 ± 6 years) during stable and exacerbation phases. Samples were assayed for NE activity utilising both ProteaseTag™ Active NE Ultra Immunoassay and a fluorogenic substrate-based kinetic activity assay. Both assays detected elevated levels of NE in the majority of patients (n = 7) during an exacerbation (mean = 217.2 µg/ml ±296.6) compared to their stable phase (mean = 92.37 µg/ml ±259.8). However, statistical analysis did not show this difference to be significant (p = 0.07, ProteaseTag™ Active NE Ultra Immunoassay; p = 0.06 kinetic assay), which is highly likely to be due to the low study number. A highly significant correlation was found between the 2 assay types (p ≤ 0.0001, r = 0.996). NE as a primary efficacy endpoint in clinical trials or as a marker of inflammation within the clinic has been hampered by the lack of a robust and simple to use assay. ProteaseTag™ Active NE Immunoassay specifically measures only active NE in clinical samples, is quick and easy to use (<3 h) and has no dependency on a kinetic readout. ProteaseTag™ technology is currently being transferred to a lateral flow device for use at Point of Care.